Comparison of the effect of collagen (amino acid) and amnion (proteinase inhibitor) on the wound healing of soft tissues - Adhiarto, Weko; Mangundjaja, Sunardhi; Yusuf, Makmuri; Pontjo, Bambang (Universitas Padjadjaran, 2010)
The wound healing process of the soft tissue aims to accelerate the closing of the wound by recurring, restoring the function, and minimizing the scar tissue. This process has to occur in the surgery process to obtain better-wound healing. The aim of this study was to know the stimulation effect of the wound dressing to accelerate the wound healing process of the soft tissue using Collagen (amino acid) and Amnion (proteinase inhibitors). This true experimental study was done to 36 mice (Sprague Dawley) that were divided into three different groups, two groups were the treatment groups and one group was the control group. Each group was adapted in Pathology Laboratory of Faculty of Veterinary Medicine Bogor Agricultural University. All of the mice were injured on the skin by incising the right side of the back for 2 cm in length and 4 mm in depth and then cleaned with 0.9% NaCl solution. To the first group of treatment, the wound was applicated by Amnion, and the second group was applicated by Collagen. Each 4 mice of all group were a termination by ether and encryption on the wounded tissue was conducted on day 3rd, 7th, and 14th. Assessment for a number of fibroblast and collagen synthesis on the wound of back tissue was conducted with the histological examination by painted using hematoxylin-eosin. The results concluded that Collagen application was influencing the mean of fibroblast higher than Amnion, and the lowest was controlled with statistically significant. The mean of collagen used Collagen lower than Amnion, and the lowest was control with statistically significant. It could be concluded that collagen application was preeminent in increasing the productivity of the fibroblast, as well as in developing forms of the collagen synthesis compared with Amnion and control.